2019
DOI: 10.1108/hff-01-2019-0083
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of drug delivery micro-circulatory system with a novel pattern of CuO-Cu/blood hybrid nanofluid flow towards a porous stretching sheet

Abstract: Purpose This paper aims to simulate the steady laminar mixed convection incompressible viscous and electrically conducting hybrid nanofluid (CuO-Cu/blood) flow near the plane stagnation-point over a horizontal porous stretching sheet along with an external magnetic field and induced magnetic field effects that can be applicable in the biomedical fields like the flow dynamics of the micro-circulatory system and especially in drug delivery. Design/methodology/approach The basic partial differential equations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…Subhani and Nadeem 16 studied the behavior of (hybrid nanofluid) over the stretching surface. Dinarvand et al 17 introduced /blood (hybrid nanofluid) circulation on a permeable stretching sheet, which is an advanced density concept, that can be a favorable model in medical sciences, particularly in cancer therapy and drug delivery. In an investigation for cancer cell therapy, Liu et al 18 examined that and are the best nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Subhani and Nadeem 16 studied the behavior of (hybrid nanofluid) over the stretching surface. Dinarvand et al 17 introduced /blood (hybrid nanofluid) circulation on a permeable stretching sheet, which is an advanced density concept, that can be a favorable model in medical sciences, particularly in cancer therapy and drug delivery. In an investigation for cancer cell therapy, Liu et al 18 examined that and are the best nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from that reported, the following recent studies, such as those by Souayeh et al [ 30 ], Ullah et al [ 31 ], and Aziz and Afify [ 32 ], can be referred to as additional knowledge correlated with the Casson NF flows. Dinarvand et al [ 33 ] demonstrated steady laminar mixed convection incompressible viscous and electrically conducting HNF (CuO- Cu/blood) flow over the plane stagnation point over a horizontal porous stretching layer with an external magnetic field, taking into account the induced magnetic field effect, which can be used in biomedical fields, especially in drug delivery. Reddy [ 34 ] investigated the model for electro-MHD flow over a stagnation point flow of HNF with non-linear thermal radiation and non-uniform heat source/sink that is implemented to blood-based NFs for two different NPs.…”
Section: Introductionmentioning
confidence: 99%
“…In Bhatti’s study [ 7 ], the properties and implementations of the vector viscosity blood clot model were investigated. The two-step model of peristalsis was considered in Dinarvand [ 8 ]. The constant laminar-blended mixture viscous and hybrid (CUO-Cu/blood) hybrid fluid flows near the plane stagnations on a level, permeable, linearly stretched board with an adjustable magnetic flux through a new nanoparticle and based liquid measurement [ 9 ].…”
Section: Introductionmentioning
confidence: 99%